PENGARUH E-COMMERCE PERUSAHAAN LAZADA TERHADAP UMKM DI INDONESIA - Rambe, Cindy Marito Purba; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research analyzed and described one of the e-commerce based companies in Indonesia. E-commerce is a buying and selling process using internet media, which can save time and can be accessed anywhere. One of the e-commerce based companies is Lazada, which has contributed to micro, small, and medium enterprises in Indonesia. Lazada is a multinational company that entered Indonesia in 2012 and has also become one of the largest marketplaces in Indonesia. In its efforts to overcome problems that often occur among micro, small, and medium businesses in Indonesia, Lazada then provides convenience for business actors who use Lazada. The theory used in this research is perspectives liberalism and multinational corporation theory. Multinational corporation Multinational corporation are non-state actors that can bring influence in the international order to the domestic realm. The author uses qualitative methods and data collection techniques through literature studies sourced from several books, journals, articles, and websites The result of this study shows condition of MSMEs in Indonesia and contributions the Lazada company makes to MSMEs under the auspices of Lazada is, holded online human resources training, provided affordable capital, easy to accsess applications, collaborations with government, to uphold standardization and quality, and given access market. Keywords: e-commerce, Lazada, MSEMs